Social Media Activities at Ulam Tawa Restaurant - Ni Ketut Wahyu Darmaja Putri; Silvanus Alvin (Indonesian Journal of Business Analytics, 2023)
One company that plays a role in the growth of category I (Accommodation and Drinking Food Providers) is Ulam Restaurant. There are many seafood restaurants on the island of Bali, but Ulam Bali has become a legendary icon because the food served is a representation of the seafood that is widely known today. research dissects in depth related to the social media marketing strategies and activities carried out by Ulam Tawa Bali restaurant. The limitation of this research is that no measurement of the success of the strategy has been carried out.